Produção de levana por Bacillus subtilis e Zymomonas mobilis utilizando três meios de cultura sintéticos e um alternativo (caldo de cana-de-açucar) - Ernandes, Fernanda Maria Pagane Guereschi [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A levana é um exopolissacarídeo constituído por unidades de frutose, unidas através de ligações (2 6), sintetizado por vários microrganismos durante a fermentação de um meio de cultura à base de sacarose, extrato de levedura e sais minerais. Este biopolímero possui diversas aplicações tanto na área de alimentos (fixador de cores e sabores, espessante e estabilizante de vários alimentos) como também na farmacêutica (substituto de plasma sanguíneo, imunomodulador, anticarcinogênico e hipocolesterolêmico). Este trabalho teve como objetivo principal estudar o processo de produção de levana através do cultivo das bactérias Bacillus subtilis e duas linhagens de Zymomonas mobilis (CP4 e CCT 4494). Durante a otimização de sua produção, foi analisado o efeito da variação de: fontes de carbono em diferentes concentrações, temperatura (25; 30 e 35°C), concentração de extrato de levedura (1,0 a 10,0%) e pH (6,0; 7,0 e 8,0). As fontes de carbono testadas foram frutose e glicose (1,0; 2,0; 3,0; 4,0 e 5,0%) e sacarose (1,0; 2,0; 3,0; 4,0; 5,0; 10,0; 15,0 e 20,0%), as quais foram adicionadas em três meios de cultura sintéticos denominados como meios 1, 2 e 3. Além destes meios, também foi testado o caldo de cana-de-açúcar, em diferentes concentrações de sólidos solúveis (10,0; 15,0 e 20,0%), como meio de cultura alternativo para obtenção de levana. Após o término do processo fermentativo, foi realizada a determinação do pH diretamente do caldo fermentado. A seguir, o caldo foi centrifugado a 8000 rpm durante 15 minutos e a biomassa foi estimada como peso seco...

Levan is an exopolysaccharide constituted by fructose units, ß (2.6) linked, synthesized by several microorganisms during fermentation of a culture medium containing sucrose, yeast extract and mineral salts. This biopolymer has various applications as much in food area (colors and flavors fixer, thickener and stabilizer of several foods) as in pharmaceutical one (blood plasma replacement, immunomodulator, anticarcinogenic and hypocholesterolemic). The principal objective of this work was to study the levan production process by cultivation of Bacillus subtilis bacteria and two strains of Zymomonas mobilis (CP4 and CCT 4494). During the optimization of its production it was analyzed the variation effect of: different concentrations of carbon sources, temperature (22; 30 and 35°C), yeast extract concentration (1.0 to 10.0%) and pH (6.0; 7.0 and 8.0). The tested carbon sources were fructose and glucose (1.0; 2.0; 3.0; 4.0 and 5.0%) and sucrose (1.0; 2.0; 3.0; 4.0; 5.0; 10.0; 15.0 and 20.0%) which were added to three synthetic culture media coded as 1, 2 and 3. Besides these media, the sugar cane broth was also tested at different concentrations of soluble solids (10.0; 15.0 and 20.0%) as alternative culture medium for levan obtainment. After the fermentative process finished the fermentation broth pH was measured. Afterwards, the broth was centrifuged at 8000 rpm for 15 minutes and the biomass was estimated as dried weight. After the analysis of the RS (reducing sugars) and TRS (total reducing sugars) in the supernatant, this was precipitated with three volumes of ethanol, driedand ground to determine the levan concentration and the ash content. After analysis of the results obtained with the different media used, it was verified that the bacteria grew at pH in a range from 4.0 to 7.5 and that levan wasn t produced at pH lower than 3.5. The results... (Complete abstract click electronic access below)
Keywords: Biopolimeros; Fermentação; Levana - Produção; Fermentação liquída; Levan